Analisis Faktor Penyebab Keterlambatan Terhadap Pelaksanaan Proyek Konstruksi - Palilati, Mifiday Putri; Doda, Nurhayati; Dwi Ma’sum, Ratna (Departement of Civil Engineering, Universitas Winaya Mukti, 2024)
Construction project implementation In general, it can be interpreted as a temporary activity that lasts for a limited period of time. When carrying out construction project work, construction project delays are very often encountered. Construction project delays are a common problem in the construction industry. Delays can occur for various reasons. This research was conducted with the aim of finding out the factors of development project delays in the high school building construction project in Gorontalo Province. Quantitative research methods are used to determine the causes of project delays by collecting data through questionnaires, S curves and work weights. The data processing method uses SPSS for Windows analysis and the help of Microsoft Excel. The results obtained from this research are the dominant causal factors that cause delays in construction projects, namely the variable (X1) Labor Factor with a mean value of 3.21, Material Factor (X2) with a mean value of 3.12 and equipment factor (X3) with a mean value of 2.94.